Współczesne wyzwania prawnej ochrony zwierząt: Strony redakcyjne i spis treści - Helios, Joanna; Jedlecka, Wioletta; Helios, Waldemar; Listos, Piotr (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2023)
This monograph presents detailed problems of legal protection of animals (pseudo-breeding, execution of animals, slaughter, welfare of hens, protection of bees, bullfights). This area is specific. Both in doctrine and practice, it causes numerous disputes, which are largely related to the lack of subjectivity of animals and their unclear status under the rules of law. The monograph reflects a large number of legal problems, including ethical, axiological and philosophical ones, which are socially significant and have value for the discourse on animals and their rights. The monograph was prepared by students and PhD students - members of the Animal Rights Scientific Circle. It is the " scientific fruit" of over six years of scientific and didactic work of all members and supervisors of the Student and Doctoral Students' Scientific Circle of Animal Rights, operating at the Department of Theory and Philosophy of Law of the Faculty of Law, Administration and Economics of the University of Wrocław.
Keywords: legal protection of animals; pseudo-breeding; execution of animals; slaughter; hens; bees; bullfighting; animal welfare